Characterization and Classification of Soils in Eastern Himalayan Agro-climatic Region: A Case Study in Nongpoh Micro-watershed of Ri-Bhoi District, Meghalaya - B.U. Choudhury, A.K. Singh, Adelbert Kharlyngdoh, Carolyn Zothansiam Pradip K. Bora, Pratibha T. Das (Journal of the Indian Society of Soil Science, 2015)
Typical pedons representing major landforms of Nongpoh micro-watershed in Ri-Bhoi district of Meghalaya viz., hill top, hill slope and inter hill valley developed from granite–gneiss occurring under varying land use were characterized, classified and assessed. The soils were deep to very deep in depth, brown to greyish brown in colour, slightly acidic to extremely acidic in reaction and high to medium in organic carbon. Further, the soils were low to high in available nitrogen, low to high in available phosphorus and medium to high in available potassium. Pedon P2 and P3 which are located on the hill top and the hill slopes, respectively showed cambic (Bw) sub-surface diagnostic horizon and were classified as Typic Dystrudepts while the hill top pedon P1 and on hill slope pedon P4, sub-surface diagnostic horizon possessed argillic (Bt) horizon which was classified as Typic Paleudalfs. However, pedons located on the inter hill valley (P5 and P6) did not exhibit any diagnostic horizon and hence were classified as Oxyaquic Udifluvents and Aeric Endoaquents, respectively.